2022
DOI: 10.25259/sni_837_2022
|View full text |Cite
|
Sign up to set email alerts
|

Antifibrinolytics use during surgery for oncological spine diseases: A systematic review

Abstract: Background: Data exist of the benefits of antifibrinolytics such as tranexamic acid (TXA) in general spine surgery. However, there are limited data of its use in oncological spine patients. Methods: A systematic review was conducted using the Preferred Reporting Items for Systematic Reviews and Meta-Analyses guidelines. PubMed, Cochrane, OVID, and Embase databases were searched. Search terms: “tranexamic acid”, “aprotinin,” “aminocaproic acid,” “spine surgery,” “spine tumors,” and “spine oncology.” Include… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 32 publications
(93 reference statements)
0
1
0
Order By: Relevance
“…In a study of adult patients surgically treated for vertebral column tumors, Pennington et al found that TXA was not associated with increased VTE risk, although high-dose TXA (≥20 mg/kg) was associated with increased odds of deep vein thrombosis (DVT) or pulmonary embolism (PE) [ 25 ]. A recent systematic review of antifibrinolytic use in adult patients ( n = 408 patients in 7 studies) undergoing spinal surgery for oncological spinal disease reports efficacy with no increased risk of DVT or PE [ 27 ]. While this information cannot be directly extrapolated and applied to neurosurgical pediatric populations, our small single center study supports this in reporting no increased thromboembolic events related to TXA in this cohort.…”
Section: Discussionmentioning
confidence: 99%
“…In a study of adult patients surgically treated for vertebral column tumors, Pennington et al found that TXA was not associated with increased VTE risk, although high-dose TXA (≥20 mg/kg) was associated with increased odds of deep vein thrombosis (DVT) or pulmonary embolism (PE) [ 25 ]. A recent systematic review of antifibrinolytic use in adult patients ( n = 408 patients in 7 studies) undergoing spinal surgery for oncological spinal disease reports efficacy with no increased risk of DVT or PE [ 27 ]. While this information cannot be directly extrapolated and applied to neurosurgical pediatric populations, our small single center study supports this in reporting no increased thromboembolic events related to TXA in this cohort.…”
Section: Discussionmentioning
confidence: 99%